A Systematic Review and Meta-Analysis of the Potential of Millets for Managing and Reducing the Risk of Developing Diabetes Mellitus - Anitha, Seetha; Kane-Potaka, Joanna; Tsusaka, Takuji W.; Botha, Rosemary; Rajendran, Ananthan; Givens, D. Ian; Parasannanavar, Devraj J.; Subramaniam, Kowsalya; Prasad, Kanaka Durga Veera; Vetriventhan, Mani; Bhandari, Raj Kumar (Frontiers in Nutrition, 2021)
Millets (including sorghum) are known to be highly nutritious besides having a low carbon footprint and the ability to survive in high temperatures with minimal water. Millets are widely recognized as having a low Glycaemic Index (GI) helping to manage and prevent diabetes. This systematic review and meta-analyzes across the different types of millets and different forms of processing/cooking collated all evidences. Of the 64 studies that were collected globally, 39 studies with 118 observations were used to analyze glycaemic index outcomes and 56 studies were used to analyze fasting, postprandial glucose level, insulin index and HbA1c outcomes in a meta-analysis. It is evident from the descriptive statistics that the mean glycaemic index of millets is 55.3 ± 20.0, which is about 30% lower than in typical staples of milled rice (71.7 ± 14.4) and refined wheat (74.2 ± 14.9). The descriptive, meta and regression analyses revealed that Job’s tears, fonio, foxtail, barnyard and teff were the millets with low mean GI (<55%) that are more effective (≥26%) in reducing dietary GI than the control samples. Millets with intermediate GI (55-69%) are pearl millet, finger millet, kodo millet, little millet and sorghum which have a 14 to 26% lower GI than the control with high GI (>69%). A meta-analysis also showed that all millets had significantly lower GI (p<0.01) than white rice, refined wheat, standard glucose or white wheat bread except little millet which had inconsistent data. Long term millet consumption lowered fasting and postprandial blood glucose levels significantly (p<0.01) by 12% and 15%, respectively in diabetic subjects. There was a significant reduction in HbA1c level (from 6.65 ± 0.4 to 5.67 ± 0.4 %) among pre-diabetic individuals (p<0.01) who consumed millets for a long period. Minimally processed millets were 30% more effective in lowering GI and the glycaemic load of a meal compared to milled rice and refined wheat. In conclusion, millets may be beneficial in managing diabetes and reducing the risk of developing diabetes and could therefore be used to design appropriate meals for diabetic and pre-diabetic subjects as well as for non-diabetic people for a preventive approach.